É a dialética uma ciência política? um estudo político-filosófico do político de Platão - Corbani, Weriquison Simer (2023)
The thesis investigates whether dialectic is a political science in Plato's Statesman. Initially, our focus was to analyze the occurrences of dialectic in the middle dialogues to understand the application of the method of hypotheses, which reaches its peak in the Republic. From there, Plato begins to make use of the method of collection and division, characteristic of his later works. The dialectic in the Statesman follows the same structure as that presented in the Sophist, except for its content. In the Statesman, the central concern is to define the exclusive science of the political man (πολιτικὸς ἀνήρ). But the task of distinguishing the competence of the politician from that of the dialectician is never easy since these themes intertwine throughout the dialogue. Considering this, the study proceeds to examine the fundamental characteristics of both in the context of the weaving paradigm, which is a paradigm for both dialectic (because it employs the syncritic and diacritic operations) and political science (because it weaves differences to produce a quality fabric). We then see, in the course of this analysis, that the production of the civic unity of the polis is only possible because the politician knows how to use a type of practical intelligence (φρόνησις) that is related to a kind of qualitative measure, taking into account opportune timing (τὸν καιρὸν), propriety (τὸ πρέπον), and the just measure (τὸ μέτριον). It is this competence that makes the politician's action prescriptive and directive (ἐπιστατική, ἀρχή). Finally, by showing the distinction and articulation between dialectic and political science, the thesis also demonstrates that the politician is the philosopher of action in practical life.